Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3109/09687637.2010.495098
|View full text |Cite
|
Sign up to set email alerts
|

Service user involvement in methadone maintenance programmes: The ‘philosophy, the ideal and the reality’

Abstract: Internationally, service user involvement has become a common feature of public policy and more specifically public health policy in the recent decades. In a general context, the involvement of service users in health services has been well documented; however, less evidence is available within the area of drug treatment service provision. This study, which was conducted in Ireland, sought to address this gap in the knowledge and understanding of service user involvement within this setting. Qualitative in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 18 publications
5
31
0
Order By: Relevance
“…Our ndings are consistent with several studies which have shown that experiential workers are not always accepted and respected in the workplace due to their history of substance use [32,33,65,66]. Some studies have also reported that support workers without lived experience of substance use have negative attitudes towards experiential workers, rooted in stereotypes and stigma towards PWUD [31][32][33]65]. These negative attitudes are apparent in the terminology used by support workers to de ne experiential workers, including "unstable," "manipulative," "untrustworthy," and "lacking capacity to participate" [31][32][33]65].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our ndings are consistent with several studies which have shown that experiential workers are not always accepted and respected in the workplace due to their history of substance use [32,33,65,66]. Some studies have also reported that support workers without lived experience of substance use have negative attitudes towards experiential workers, rooted in stereotypes and stigma towards PWUD [31][32][33]65]. These negative attitudes are apparent in the terminology used by support workers to de ne experiential workers, including "unstable," "manipulative," "untrustworthy," and "lacking capacity to participate" [31][32][33]65].…”
Section: Discussionsupporting
confidence: 93%
“…This explains why 40% of the survey participants listed "work situation, including working conditions" as one of their top three stressors. Our ndings are consistent with several studies which have shown that experiential workers are not always accepted and respected in the workplace due to their history of substance use [32,33,65,66]. Some studies have also reported that support workers without lived experience of substance use have negative attitudes towards experiential workers, rooted in stereotypes and stigma towards PWUD [31][32][33]65].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Her study suggests that despite the fact that providers understand the potential benefits of incorporating client experiences into the drafting delivery and assessment of services they remain ‘passive players’ in the equation [ 31 ]. Over the intervening time, Irish research has attempted to address this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…The articles by Randall (2011) and King (2011), dealing respectively with the rationality of drug policy and with service user involvement in drug treatment and rehabilitation systems, reflect themes which are to be found more or less universally within modern, managerial-type, drug strategies. Randall uses mixed methods in her quest for the elusive research-policy interface within the Irish drug policy process, before concluding that no such interface exists and that drug policy is unlikely to ever attain the degree of rationality suggested by the managerial rhetoric of current policy documents.…”
mentioning
confidence: 98%